Kemiskinan dan Lingkungan : Kasus Komunitas Lahan Basah Kota di Depok dan Jakarta - Lubis, Rissalwan Habdy (UI Scholars Hub, 2006)
There are relationship between environmental issues and other issues that enclose to the human life. There are two dimensions of Environmental contex, namely: physical spatial context and social context. In fact, anthropogenic activities have serious impacts to the damage of the environment. The relation between environmental issues and poverty is very complex. The World Bank identified three main relations between the degradation of environmental condition and the living condition of poor people, namely: the environmental health, the livelihoods of poor people,and the vulnerability of people living below poverty line.